Quality of life of end-stage renal disease patients - Oshima, Rie; Kato, Yasuko; Ushida, Yumiko (Journal of Japanese Society for Dialysis Therapy, 1991)
In order to achieve psychosocial adjustment, end-stage renal disease (ESRD) patients require not only adequate medical services but social services as well. As a means of evaluating the psychosocial adjustment of ESDR patients, they were asked to reply to questionnaires concerning their sociodemographic background, employment status and feelings regarding social insurance and services. In February, 1989, 273 ESRD patients at the Kidney Center of Nagoya Daini Red Cross Hospital under 60 years of age were asked to fill out questionaires. Replies were obtained from 184 patients (67.3%). Of these 184 patients, 52 patients were treated by regular hospital hemodialysis, 19 patients by CAPD, and 113 patients had functioning kidney transplants. 1. ESRD patients in our kidney center were more satisfied with their quality of life (QOL) than healthy subjects, and patients with transplants were the most satisfied of the three groups of ESRD patients. 2. About 40% of the ESRD patients were dissatisfied with their employment status. And about half of the patients who did not receive vocational rehabilitation could not find satisfactory employment. About 60% of the ESRD patients thought that they did not have the benefit of employment and were not satisfied with the work environment. 3. Most ESRD patients were dissatisfied with social services and were anxious about social insurance, especially their economic status. Thus, ESRD patients were satisfied with their QOL, but were anxious about the future, especially their economic status and insurance, because they were dissatisfied with their work environment. In order to achieve satisfaction in ESRD patients, it is important to establish adequate social services and information concerning social services and insurance.